2005
DOI: 10.1021/jp045352x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Effects on Optical Properties of CdSe Nanocrystals

Abstract: We report effects of various organic and inorganic ligands on optical properties of CdSe nanocrystals (NCs) by changes in their photoluminescence and absorbance spectra. Surface ligand loss occurring during dilution and purification of solutions of CdSe NCs leads to a decrease of photoluminescence intensity. The complex of trioctylphosphine with Se atoms on the surface of CdSe NCs is found responsible for the trap emission band that is red-shifted relative to the photoluminescence band edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
487
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(522 citation statements)
references
References 50 publications
31
487
3
1
Order By: Relevance
“…The enlargement of the emission band for QDs in THF compared to the QDs in toluene is probably due to a more inhomogeneous distribution of crystallite size and/or impurities of the QDs solution. 22,23 As oppose to the solution in toluene, the solution of PMMA-encapsulated QDs in THF was inhomogeneous, with PMMA microparticles that could be seen by naked eye. These inhomogeneities perturbed the reproducibility of the measurements.…”
Section: A Materialsmentioning
confidence: 99%
“…The enlargement of the emission band for QDs in THF compared to the QDs in toluene is probably due to a more inhomogeneous distribution of crystallite size and/or impurities of the QDs solution. 22,23 As oppose to the solution in toluene, the solution of PMMA-encapsulated QDs in THF was inhomogeneous, with PMMA microparticles that could be seen by naked eye. These inhomogeneities perturbed the reproducibility of the measurements.…”
Section: A Materialsmentioning
confidence: 99%
“…It is difficult to reproducibly apply chemical and biochemical procedures to these QDs because of their unstable nature. In addition to the use of thiol molecules to cap the surfaces of CdSe QDs, most researchers used various amines as ligands to modify the optical properties of CdSe QDs [40][41][42][43][44]. Talapin et al synthesized CdSe QDs in a three-component hexadecylamine (HDA)-trioctylphosphine oxide (TOPO)-trioctylphosphine (TOP) mixture [35].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that PL efficiency losses are caused by insufficient passivation of the surface traps. Murray et al examined the effect of the surface modification of CdSe QDs on the optical properties [45]. They interpreted the substantial increase in PL intensity following the addition of HDA molecules as the elimination of nonradiative decay pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The ligands act as an insulator or a carrier trap site that interrupts carrier transport from the active layer to electrode. 13 In the past we also reported that the inverted structure using fluorine-doped tin oxide (FTO) can improve the device performances with higher stability and efficiency.…”
Section: 12mentioning
confidence: 99%